Moderating role of corruption control on firm level determinants of corporate sustainability disclosure compliance in Nigeria - Bello, Mohammed Sabo; Mohd Said, Ridzwana; Johari, Jalila; Kamarudin, Fakarudin (Editorial Universidad de Almería, 2021)
This paper explores the moderating effect of corruption control in strengthening the influence of firm attributes on corporate sustainability disclosure compliance in Nigeria. The study focuses on the existing discussion on mandatory disclosure compliance with a corporate governance code. The extent of disclosure compliance is measured using a total unweighted disclosure index, developed from a panel data set of 118 companies listed on the Nigerian capital market. The companies were selected using a proportionate stratified sampling technique. The dataset for the period of 2011 to 2017 were first analyzed by static panel regression analysis. The regression models were subjected to further robustness checks under dynamic GMM panel regression analysis, to test for possible endogeneity. The findings revealed the significant moderating effect of corruption control, evidenced from the interaction of corruption control with selected firm attributes, namely; industry type, leverage and taxation. The research contributes to the existing literature, as it establishes the importance of control of corruption as an additional factor of corporate sustainability disclosure compliance within the context of Nigeria.